Patterns of variation in wing venation of Iberian Cordulegaster boltonii (Donovan, 1807) (Odonata: Cordulegastridae) - Nunes, Luísa (2023)
Some structural characters, such as wing venation, have been used in odonates to differentiate taxa. In Cordulegaster boltonii, a species widely distributed throughout the western Palaearctic, the main characteristics of its wing venation have not been quantified until now. A six-variable analysis of wing venation (number of antenodal and postnodal cross-veins, number of cells in the anal triangle and in the anal loop) in specimens from several European countries was carried out. The results showed that: (a) females had a greater number of transversal veins and cells in the anal loop than males; (b) the values of these four variables were significantly lower in males from the Iberian Peninsula than in those from elsewhere; (c) within the Iberian Peninsula two groups of populations can be distinguished: one covers the north and the other the rest of the peninsula, the latter with two subgroups, one in the centre and one in the south and east. The number of cells in the anal loop is a valid variable for analyzing geographic differences in this species.